2020
DOI: 10.1558/ijsll.40571
|View full text |Cite
|
Sign up to set email alerts
|

Who owns your voice? Linguistic and legal perspectives on the relationship between vocal distinctiveness and the rights of the individual speaker

Abstract: Only in very recent times has the concept of 'ownership' of a human voice begun to demand proper consideration in terms of its legal implications. The current lack of clarity with respect to the rights afforded to individuals and organisations in this area is something that must be addressed as a matter of some urgency, given that voice samples are now collected on an unprecedented scale, with or without the knowledge or consent of the person(s) who produced the captured speech. In this paper we explore the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Voice data are unlikely to be the first type of data that come to mind with respect to data protection concerns. [10] discuss the concept of "voice ownership" and how this relates to data protection issues. Within their exploration, they illustrate how it is becoming a very real possibility that voice data could be used in a fraudulent way, particularly given the rise in speaker recognition technologies as access mechanisms for digital accounts (such as online banking).…”
Section: Data Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Voice data are unlikely to be the first type of data that come to mind with respect to data protection concerns. [10] discuss the concept of "voice ownership" and how this relates to data protection issues. Within their exploration, they illustrate how it is becoming a very real possibility that voice data could be used in a fraudulent way, particularly given the rise in speaker recognition technologies as access mechanisms for digital accounts (such as online banking).…”
Section: Data Protectionmentioning
confidence: 99%
“…Underlying the research efforts in [10] and [11] has been the broader increase in awareness across sectors, and the public, with respect to data protection and privacy. This increase in awareness is reflected in legislation and court rulings.…”
Section: Data Protectionmentioning
confidence: 99%
“…A decade ago, Yamagishi et al [3] (p. 1) outlined that "it is not easy, and certainly not cost effective, for manufacturers to create personalized synthetic voices". However, technology has sufficiently matured to realistically emulate individual speakers' voices electronically [12]. Researchers have shown that the results of new speech-synthesis systems are good enough to mislead listeners to thinking that they are listening to authentic voices when they are in fact synthetic [13][14][15].…”
Section: Introductionmentioning
confidence: 99%